PENGEMBANGAN ALAT PEMBELAJARAN BERBASIS ARTICULATE STORYLINE DENGAN APLIKASI ZOOM SEBAGAI MEDIA PERANTARA PADA MATA PELAJARAN DASAR DESAIN GRAFIS DI ERA PANDEMI COVID-19 - Ayu Annisa Akbar; Lista Litta (Antivirus : Jurnal Ilmiah Teknik Informatika, 2021)
The world is suffering by the Covid-19 pandemic which all activities including the learning process is having trouble. Thus, the Indonesian government provides a solution is all the learning process should be at home. The teaching and learning process is carried out by online. The reduced interest in student learning becomes a problem that occurs during online learning, therefore teachers must create a lesson that can increase students interest and motivation in learning. One interesting learning application creator is is the Articulate Storyline. Articulate Storyline is an application for making learning tools. This research was made using the RnD method. This method includes initial analysis, product design and design, product manufacture to testing. In this study, the results obtained that the validity level was 83.80%, the practicality level was 92.24% and the effectiveness level was 96.47% so that the learning tools produced in this study could attract students' interest in learning in the pandemic era.